Analysis of Career Planning for Students Based on Career Guidance Theory - Tila Rohimah; Daharnis Daharnis; ifdil ifdil (Jurnal Psikoedukasi dan Konseling, 2025)
This study aims to analyze the application of Holland's theory in career planning for students through career guidance at school. Holland's theory, which divides human personality into six types (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional), can be used to help students understand the match between their personality type and the appropriate work environment. With this approach, it is expected that students can choose a more purposeful career path, reduce dissatisfaction, and increase the potential for future success. This research uses the literature study method by collecting and analyzing the results of previous research related to the application of Holland's theory in career guidance. The results show that although Holland's theory provides a clear framework in helping students plan careers, its implementation requires a deep understanding from counselors as well as environmental support such as family and education. In addition, web-based technology can increase the accessibility of personality assessment for students, but still requires proper guidance from counselors to ensure effective use. Overall, the application of Holland's theory in career guidance can provide significant benefits in helping students plan a career that is more in line with their potential and aspirations.